Wisdom Local Tegal City Communities in the Modernization Era and Strategies to Maintain It - Jamika, Fadel Ikrar; Barlian, Eri; Erianjoni, Erianjoni; Umar, Iswandi; Fatimah, Siti (Balai Publikasi Indonesia, 2023)
Indigenous peoples are generally very familiar with their environment. Human nature as a culture being is understood ecologically as one of connected environments. Indigenous peoples' view that humans are an integral part of nature and act responsibly, respectfully and compassionately towards the survival of the universe. Local wisdom as traditional knowledge of nature conservation and environmental protection is regarded as highly valuable and brings many benefits to human life. Purpose of the study It is to describe the holistic and internal strategy to maintain the local wisdom of Tegal public city in the era of modernization. The methods used are qualitative literature or review literature. The Wisdom local of Tegal city exists to this day, the tradition of resident town Tegal for drinking tea, Muti tradition of Tegal city community, Upload tradition of Tegal city community, and Eid Al-Fitr is called Fitri in Tegal City parish. is traditionally used. Strategies are implemented to preserve the wisdom of field scores in an era of modernization: Instill a love of culture in society, host cultural festivals, promote culture, and create culture as an identity.